2009
DOI: 10.1094/phyto-99-6-0775
|View full text |Cite
|
Sign up to set email alerts
|

Infection Dynamics of Fusarium mangiferae, Causal Agent of Mango Malformation Disease

Abstract: Conditions affecting germination and growth of Fusarium mangiferae, causal agent of mango malformation disease, were studied in vitro. Both conidial germination and colony growth required temperatures >5 degrees C and reached a peak at 28 and 25 degrees C, respectively. A minimum 2-h wetness period was required for conidial germination, reaching a peak after 8 h of wetness. High incidence of fungal colonization in buds, predominantly the apical buds, was detected compared with inoculated leaves. The pathogen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…At least in the case of the mango bud mite, we are convinced that this is not the case because it was demonstrated that the mite can vector the spores to the buds, the fungus's sole port of entry to the plant and enhance disease severity (Gamliel-Atinsky et al 2009b). Furthermore, the spores could benefit from the ability of the mites to travel long distances by wind (Zhao and Amrine 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least in the case of the mango bud mite, we are convinced that this is not the case because it was demonstrated that the mite can vector the spores to the buds, the fungus's sole port of entry to the plant and enhance disease severity (Gamliel-Atinsky et al 2009b). Furthermore, the spores could benefit from the ability of the mites to travel long distances by wind (Zhao and Amrine 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Results from our recent study demonstrated that the apical bud is the exclusive penetration site for the fungal pathogen (Gamliel-Atinsky et al 2009b) which also serves as the exclusive living habitat of A. mangiferae. Most conidia of F. mangiferae disseminate in the air and randomly fall on the tree canopy which takes up most of the surface area of the orchard.…”
Section: Bearing Conidia On or Within The Body Of Aceria Mangiferaementioning
confidence: 96%
“…Malformed panicles, which can persist on the tree until the following season as dry, black masses, serve as sources of inoculum for as long as they remain on the tree (Fig. 3E) (22). MMD etiology.…”
Section: The Disease and Pathogensmentioning
confidence: 99%
“…The distribution of F. mangiferae in affected trees suggests that apical buds are the primary sites of infection and that systemic colonization of branch tissues does not occur (21,22,57). In Flor ida, F. mangiferae was restricted almost entirely to malformed floral and vegetative tissues (57).…”
Section: New Insights Into MMD Epidemiology and Disease Managementmentioning
confidence: 99%
“…5 Malformation is not only well-known in India but has also been confirmed in most mango-growing countries such as Pakistan, the Middlle East, Egypt, South Africa, Brazil, Sudan, Central America, Mexico, United States, Cuba, Malaysia, Australia, Israel, UAE and Bangladesh. [6][7][8][9][10] There are several confusions in the literature to explain the nature of this malady because research efforts made up to now have not been Malformation is arguably the most crucial disease of mango (Mangifera indica L.) at present. It is receiving great attention not only because of its widespread and destructive nature but also because of its etiology and control is not absolutely understood.…”
Section: Introductionmentioning
confidence: 99%